Reliability of Stereotactic Radiofrequency Ablation (SRFA) for Malignant Liver Tumors: Novice versus Experienced Operators - Peter Schullian; Gregor Laimer; Edward Johnston; Daniel Putzer; Gernot Eberle; Gerlig Widmann; Yannick Scharll; Reto Bale (Biology, 2023)
Purpose: To compare the results of a novice with those of experienced interventional radiologists (IRs) for stereotactic radiofrequency ablation (SRFA) of malignant liver tumors in terms of safety, technical success, and local tumor control. Methods: A database, including all SRFA procedures performed in a single center between January 2011 and December 2018 was retrospectively analyzed. A total of 39 ablation sessions performed by a novice IR were compared to the results of three more experienced IRs. Comparative SRFA sessions were selected using propensity score matching considering tumor type, age, sex, tumor size, and tumor number as matching variables. Overall, 549 target tumors were treated in 273 sessions. Median tumor size was 2.2 cm (1.0–8.5 cm) for 178 hepatocellular carcinomas (HCCs) and 3.0 cm (0.5–13.0 cm) for 371 metastases. A median of 2 (1–11) tumors were treated per session. Results: No significant differences were observed when comparing the results of more experienced IRs with those of a novice IR regarding the rates of major complications (6.8% [16/234] vs. 5.1% [2/39]; p = 0.477), mortality (1.3% [2/234] vs. 0% [0/39]; p = 0.690), primary technical efficacy (98.5% [525/533] vs. 98.9% [94/95]; p = 0.735), and local recurrence (5.6% [30/533] vs. 5.3% [5/95]; p = 0.886). However, the median planning/placement time was significantly shorter for the experienced IRs (92 min vs. 119 min; p = 0.002). Conclusions: SRFA is a safe, effective, and reliable treatment option for malignant liver tumors and favorable outcomes can be achieved even by inexperienced operators with minimal supervision.